Indonesian Airspace Sovereignty After the Jakarta and Singapore Flight Information Region Adjustment From the Perspective of International Law - Jupri, Jupri Yanus Halawa; Ledy Diana; Maria Maya Lestari (jurnal.unprimdn.ac.id, 2025)
Indonesia, as one of the largest archipelagic states, possesses a vast and strategically significant airspace intersecting some of the busiest international flight routes in the Asia-Pacific region. The management of this airspace is critical to upholding national sovereignty and security. However, parts of Indonesia’s strategic airspace, particularly over the Riau Islands and Natuna, remain under Singapore’s control through the delegation of the Flight Information Region (FIR). The 2022 FIR boundary adjustment agreement between Jakarta and Singapore is seen as a diplomatic milestone that expands Jakarta FIR coverage. Nonetheless, it controversially extends the delegation of air navigation management up to 37,000 feet to Singapore in sectors A and B. This situation raises concerns over the full exercise of Indonesia’s air sovereignty, as mandated by Article 1 of the 1944 Chicago Convention and Article 458 of Law No. 1/2009 on Aviation. This normative legal research, based on literature and interviews, finds that the agreement does not significantly alter Indonesia’s legal sovereignty. It also highlights disparities in FIR management and recommends that Indonesia develop a revised roadmap toward full FIR control, treating the Riau and Natuna airspace as a critical border area requiring absolute sovereignty.